Deposition of Fluid and Toxins in Severe Surgical Endotoxicoses - A. G. Rozhkov; V. I. Karandin; M. I. Tsarev; R. M. Nagayev; A. Yu. Makshantsev (Общая реаниматология)
Objective: to study the mechanisms responsible for the deposition of fluid and toxins in severe surgical endotoxicosis. Materials and methods. The reasons for triggering the mechanisms of deposition of fluid and toxins were clarified in an experimental study on animals (10 dogs) that were divided into 2 groups. All the animals were daily monitored for blood and central lymph toxicities, total circulating blood volumes, and body weight changes during natural (Group 1) and accelerated (Group 2) lymphokinesis. Whether the interstitium could be unloaded from deposited fluid and toxins was investigated in 56 patients with severe endotoxicosis. Results. In severe surgical endotoxicoses, fluid and toxins are deposited in the first days of the disease. The main reason for triggering the mechanism of deposition is the level of toxemia. The depositing process proceeds in two stages. Thoracic duct cannulation with external lymph drainage is the most effective way of unloading the interstitium from fluid and toxins. Key words: endotoxicosis, toxin deposition, interstitial space.